1996
DOI: 10.1111/j.1751-0813.1996.tb07566.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods to assess dog owners' therapeutic compliance

Abstract: Electronic monitoring provided valuable information on dose timing and variation, but proved costly and difficult to employ in veterinary practice. Simplicity and low cost of return medication counts makes this method attractive for use in veterinary compliance studies. Client self-reports reliably detected some noncompliers and permitted identification of individual problems or errors. For practical purposes a combination of return medication counts and client self-reports may have merit in future veterinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 10 publications
1
26
0
4
Order By: Relevance
“…These findings are in agreement with results of other studies 6,7,21,22 in the human and veterinary literature. Median compliance rates ranged from 64% to 100%, depending on the method of assessment, with the lowest value occurring when compliance was defined as the proportion of doses given on time.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with results of other studies 6,7,21,22 in the human and veterinary literature. Median compliance rates ranged from 64% to 100%, depending on the method of assessment, with the lowest value occurring when compliance was defined as the proportion of doses given on time.…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective study design was chosen to accurately measure real life treatment patterns. Prospective study designs can inflate adherence because individuals know they are being tracked, which consequently improves their behaviour . Because there is a high risk of discontinuing treatment after the initial prescription for a treatment, this study evaluated ASIT orders to the first refill and it provides no information on long‐term ASIT use …”
Section: Discussionmentioning
confidence: 99%
“…Fluctuating peak and trough plasma and urine concentrations of an antimicrobial may be exacerbated with poor owner compliance and animals that are difficult to administer the tablets. Several authors have attempted to assess the extent of owner compliance with dosing and reports show 44 to 84 per cent compliance (Barter 1996, Grave 1999). Owners who participated in the study reported here were chosen because of their commitment and ability to dose their dogs; and yet, six per cent of the dogs (eight of 129) were not dosed according to instructions and were administered more than 20 per cent additional doses.…”
Section: Discussionmentioning
confidence: 99%